Oxidative stress and antioxidant status among the elderly in Jakarta - Novi Silvia Hardiany; Daniya Qanita Amani; Jasmine Virginia Anjani; Prima Christin Natalia; Rheina Tamara Tarigan (Acta Biochimica Indonesiana)
Background: Indonesia is experiencing a demographic shift, with the elderly population comprising 9.92% (26.82 million) of the total population, 8.21% of whom reside in Jakarta. Oxidative stress is a key contributor to the development of degenerative diseases associated with aging, while antioxidant defenses can mitigate its effects.